2015
DOI: 10.1515/hukin-2015-0048
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Mixed Martial Arts Spectators’ Motives and their Sports Media Consumption in Poland

Abstract: The study attempted to analyse the concept of spectators’ motives at mixed martial arts (MMA) events in Poland. In addition, we investigated the relation between motives and sports media consumption. The sample consisted of 273 people attending three similar, regional MMA events. Exploratory factor analysis was used to refine the structure of motives. Confirmatory factor analysis showed a reasonable fit of the obtained model (RMSEA = 0.41). Using ANOVA we found three significant differences in assessment of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…While the mainstream coverage focused on producing a general blaming of the martial art as a multiplier of violent and unhealthy pedagogies, the community of fans delved more deeply into various aspects of MMA’s relationship to the physical and mental health of its participants. Notwithstanding the fact that one might expect a generally absolutist tone towards MMA from those who are its fans–though partially this has certainly been the case–this event has been an opportunity to question and explore various issues of this combat sport from those who are supposed to be more inclined to defend it ( Frederick et al, 2012 ; Zembura and Żyśko, 2015 ). It was in fact the potential well-being that MMA would fail to bring to their followers that eventually leads many commentators to question the belonging of MMA to the family of martial arts, which in contrast are mostly perceived as helpful places in which to experience physical and mental growth ( Fuller and Lloyd, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the mainstream coverage focused on producing a general blaming of the martial art as a multiplier of violent and unhealthy pedagogies, the community of fans delved more deeply into various aspects of MMA’s relationship to the physical and mental health of its participants. Notwithstanding the fact that one might expect a generally absolutist tone towards MMA from those who are its fans–though partially this has certainly been the case–this event has been an opportunity to question and explore various issues of this combat sport from those who are supposed to be more inclined to defend it ( Frederick et al, 2012 ; Zembura and Żyśko, 2015 ). It was in fact the potential well-being that MMA would fail to bring to their followers that eventually leads many commentators to question the belonging of MMA to the family of martial arts, which in contrast are mostly perceived as helpful places in which to experience physical and mental growth ( Fuller and Lloyd, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…pressure from coaches, managers, organisers of MMA events, the media and fans to fight under conditions entailing risk of health loss, including sudden competition schedule changes and cases where the competitor takes part in the commercial gala even if they believe themselves to be inadequately prepared to fight or appear to be indisposed. Pressure from fans is also potent, since galas are organised for fans because of their interest The strongest motives for watching MMA are the drama of the show and hence the entertainment factor (Andrew et al, 2009;Kim et al, 2009) and fighters' performance (Zembura and Z ̇ys ḱo, 2015) 3 .…”
Section: Discussionmentioning
confidence: 99%
“…That is, spectators declare seeking skillfulness in the MMA, opposite to beliefs popular in some circles [3,39]. However, this result along with the variety of studies in the context of MMA where aesthetics is ranked as one of the most important spectators' motives [15,16,18,40] may be considered contradictory to the conclusions from the comparison of motivational patterns between fans of nonaggressive and aggressive sports [41,42]. Wann et al [41] found that fans of nonaggressive sports rate aesthetic motivation higher than fans of aggressive sports and concluded that aggressive sports seem to be less likely consumed for aesthetic reasons.…”
Section: Discussionmentioning
confidence: 99%